The Murmuring-In-Between: Eco-centric Politics in The Girl Who Swam Forever - Gray, Nelson (Theatre Research in Canada / Recherches théâtrales au Canada, 2010)
Viewing one of Clements’s earliest plays through an eco-critical lens reveals how this playwright manages to situate her post-colonial politics within a vision of the world that is unequivocally eco-centric. After detailing how Clements incorporated three primary sources in the conception and development of The Girl Who Swam Forever, this paper (employing Tim Ingold, Christopher Manes, Val Plumwood, Akira Lippit, Thomas King, and Jeanette Armstrong ) shows how the animist assumptions that inform the play’s action are fundamentally distinct from conventional Western ways of seeing. The paper then concludes by arguing that it is precisely this animist sensibility that provides Clements’s female protagonist with what Deleuze and Guattari have called "a line of escape" from the repressive constraints of human-centred thought, enabling her to imagine a world beyond the racist one that threatens to undermine her agency, well-being and self-respect. Résumé Lorsqu’on examine l’une des premières pièces de Clements en adoptant une perspective écocritique, on voit à quel point cette dramaturge a réussi à inscrire ses politiques postcoloniales à l’intérieur d’une vision du monde qui est catégoriquement écocentrique. Après avoir décrit en détail comment Clements fusionne trois sources primaires dans la conception et le développement de The Girl Who Swam Forever, cette étude démontre (en s’appuyant sur des écrits de Tim Ingold, Christopher Manes, Val Plumwood, Akira Lippit, Thomas King et Jeanette Armstrong) comment les hypothèses animistes qui informent l’action de la pièce diffèrent fondamentalement des façons conventionnelles de voir les choses en Occident. L’étude fait valoir que c’est cette sensibilité animiste, justement, qui donne à la protagoniste de Clements ce que Deleuze et Guattari ont appelé «.une ligne de fuite.» pour échapper aux contraintes répressives de la pensée centrée sur l’être humain, lui permettant d’imaginer un monde situé au-delà de l’univers raciste qui menace sa fonction d’agent, son bien-être et son estime de soi.